When the news broke : Chicago 1968 and the polarizing of America - Hendershot, Heather (The University of Chicago Press, 2022)
"Heather Hendershot argues that a moment long understood as sitting at the crux of American political history-the chaos of the 1968 Democratic convention in Chicago-is also crucial to understanding the country's media history. By scrutinizing those events and broadcasts in precise detail, Hendershot documents the emergence of the idea that the media are inherently liberal. As she shows, the public was unwilling to accept what was happening, and when exposed to even a fraction of the chaos, recoiled at what they thought could only be the malicious bias of the gatekeepers of the airwaves"--